Hyperamylasemia Post Living Donor Nephrectomy Does Not Relate to Pain - Bellini, Maria Irene (Cureus, 2020)
Introduction The aetiology of pain after laparoscopic donor nephrectomy remains unclear. Given the proximity of the left kidney to the tail of the pancreas, we aimed to assess whether mobilisation and retrieval of the left kidney might inflame the pancreas, leading to pain and hyperamylasaemia in the post-operative period. Patient and methods In the present study, 16 consecutive live kidney donors were analysed in the same three months period. Amylase levels were measured on days 1 and 2. For each 24-hour period post-operatively analgesia consumption was recorded, as well as pain scores at rest on a visual analogue scale (VAS). Results Three out of 16 donors presented hyperamylasemia. A multiple regression analysis found levobupivacaine dose, propofol dose, transversus abdominis plane block and day 1 amylase did not significantly predict pain scores. Interestingly, body mass index significantly correlated with increased pain scores (p = 0.041). Also, increasing CO2 insufflation pressure and use of local anaesthetic infusion catheters predicted a decreased deep pain score (p = 0.036 and p = 0.037). Conclusion There was no correlation of amylase levels and pain scores. Pancreatitis is a rare complication of nephrectomy and no overt cases were seen in the case of donor nephrectomy.